DETERMINATION OF RADON EXHALATION RATE FROM SOME SELECTED BUILDING MATERIALS IN SAMARU, ZARIA-NIGERIA (FUDMA JOURNAL OF SCIENCES, 2023)
In this study, Radon exhalation rate of some selected building materials in Zaria was measured and analyzed using a closed chamber method and an electronic radon detector. Each sample was placed in a container of 0.075 m3 volume for 48 hours. The results obtained from the selected building materials indicated that wood has the highest exhalation rate of 0.79 Bq/kgh while gravel has the least with an exhalation rate of 0.44 Bq/kgh. Of all the selected building materials measured, the radium content is below that of the recommended limit according to OECD which implies they pose no indoor radiation risk
Keywords: Radon concentration, Electronic radon detector, Wood, Gravel, OECD